EVALUATION OF PHYSIOLOGICAL RESPONSE TO STRESS USING FUZZY LOGIC - Wijayanto Putro, Wisnu (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
The human stress level is rather intangible, and therefore cannot be directly measured. However, this stress can be correlated to external and/or internal factors, which are rather tangible things, such as heart rate, Systolic-Diastolic Blood Pressure, salivary Î±-amylase, and skin temperature. These factors measurements are provided in wide ranges and vary individually lends itself naturally to fuzzy sets and fuzzy logic. This research is aimed at assessing respondents stress level through the changes of physiological factors above over time. The subjects of this study are 10 healthy adults, aged between 23-35 years old. The measurement time divided into four periods, namely pre-stressor, stressor-I, stressor-II and post stressor period. Pauli-test and mental arithmetic test was used as stressors. Obtained data were analyzed using Fuzzy Inference System (FIS) toolbox in MATLAB. By using fuzzy inference system model, the system succeeds to predict subject stress value/index based on subject physiological value. The result showed that the changes in human factors affects human stress value/index, although the subjects stated that their stress level on the same level their physiological factors were changed during measurement, and the models showed the changes of subject stress value during different period of measurement time.Â Keywords:Â